2009
DOI: 10.1007/s00423-008-0446-8
|View full text |Cite
|
Sign up to set email alerts
|

No relevant difference in quality of life and functional outcome at 12 months’ follow-up—a randomised controlled trial comparing robot-assisted versus conventional laparoscopic Nissen fundoplication

Abstract: The present study did not show any benefit for RALF over CLF regarding QOL and functional outcome at 12 months' follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 29 publications
3
46
0
Order By: Relevance
“…Morino et al [32] reported that ''computer-generated random numbers'' and ''sealed opaque envelopes'' were used. Muller-Stich et al [27,30] provided methodological information that ''only patients were blinded'' from the full text, and via email they stated: ''We performed a computer randomization with differing block sizes. The conceal allocation was with envelopes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Morino et al [32] reported that ''computer-generated random numbers'' and ''sealed opaque envelopes'' were used. Muller-Stich et al [27,30] provided methodological information that ''only patients were blinded'' from the full text, and via email they stated: ''We performed a computer randomization with differing block sizes. The conceal allocation was with envelopes.…”
Section: Resultsmentioning
confidence: 99%
“…A few studies were excluded from meta-analysis of different outcomes for the following reasons: only satisfaction scores of physician and nurse between HER-MES-assisted and non-HERMES-assisted laparoscopic antireflux surgery were evaluated by Luketich et al [25], median data without range value were given [26], and only outcomes of midterm follow-up were provided [27].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Single-incision surgery may prove to give an additional beneit to the use of robotics in surgery by providing steady threedimensional image and intuitive instrumentation through a single 2.5 cm incision. Results of robotic fundoplication have been promising from numerous studies [9][10][11][12][13][14][15]; but up to now, supporters failed to publish an evidence-based proof of its superiority versus existing laparoscopic techniques [16][17][18].…”
Section: Future Perspectives-single-site Robotic Nissenmentioning
confidence: 99%
“…Several studies [five prospective randomized controlled trials (RCTs)] have compared robotic and conventional laparoscopic total fundoplication for GERD (5)(6)(7)(8)(9). For instance, we randomized 50 GERD patients to robot-assisted fundoplication (n=25) or to standard laparoscopic fundoplication (n=25) (6).…”
Section: Robotic Fundoplication For Gerdmentioning
confidence: 99%